1974
DOI: 10.1016/0584-8539(74)80047-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural information from OH stretching frequencies monohydric saturated alcohols

Abstract: Al&act-Infrareddata have been recorded of the hydroxyl stretching band for about 70 monohydrie saturated alcohols in dilute carbon tetrachloride solution. The wavenumber maximum, the half-bsndwidth and the band pattern could be related to the stru&ure of the molecules. Not only primary, secondary and tertiary alcohols cau be distinguished but also @-branched and cyolic ones. Four effects seem to be connected with the OH stretching band; viz. substitution and Gxation both lowering the frequency, and rotation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…• alcohol, [23][24][25]) arising from the three internal rotational conformations of the OH group [26,27]. This interpretation is supported by the report of Emmeluth et al [28], who state, in respect of ethanol, "... in the monomer where the accepted experimental gas phase t/g splitting (refs 15 & 32 therein) amounts to 16-17 cm −1 ."…”
Section: Oh Stretch Doubletsupporting
confidence: 75%
“…• alcohol, [23][24][25]) arising from the three internal rotational conformations of the OH group [26,27]. This interpretation is supported by the report of Emmeluth et al [28], who state, in respect of ethanol, "... in the monomer where the accepted experimental gas phase t/g splitting (refs 15 & 32 therein) amounts to 16-17 cm −1 ."…”
Section: Oh Stretch Doubletsupporting
confidence: 75%
“…Chemical shift estimated errors: ±0.3 ppm for Dm 1/2 < 500 Hz, ±0.5 ppm for Dm 1/2 > 500 Hz. [420,423,424,427,[432][433][434][435][436][437] and without direct M-O bonds [438,439]. The influence of a silicon substituent on the 17 O chemical shifts is smaller or even opposite to that of an oxygen-carbon substituent, as shown in Eqs.…”
Section: Oxygen Bonded To Siliconmentioning
confidence: 98%
“…It was shown that equilibria exist between conformations in which the O H proton is associated with the .rr system and those in which it is free. The relative abundances of these conformations differ appreciably from those found in the vapour state (14)(15)(16)(17)(18)(19)(20)(21)(22). The O H stretching frequencies and relative intensities of the O H bands are dependent upon the conformations, which in turn are influenced by substitution in the vicinity of the carbinol and olefinic carbons.…”
Section: Introductionmentioning
confidence: 89%
“…Recent advances in the study of the O H stretching frequency in dilute solution, using FT-IR, have allowed structural correlation with band position to be made with great accuracy (12)(13)(14)23), and structural elucidations of certain natural products have been made (1 1). The purpose of this paper is to show that measurement of the O H stretching frequency, alone, is capable of giving detailed information regarding the nature 'Author to whom correspondence may be addressed.…”
Section: Introductionmentioning
confidence: 99%